2008
DOI: 10.1520/jai101122
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Thermodynamic Calculations to Metallurgical Studies of Multi-Component Zirconium Based Alloys

Abstract: The Zircobase thermodynamic database for zirconium alloys coupled with Thermo-Calc software represents a powerful tool for prediction of thermodynamic and metallurgical data such as activities, formation enthalpies, phase transformation temperatures, solubility limits, existence temperature range, and chemical compositions of second phase precipitates. This database was built up with binary and ternary descriptions assessed according to the CALPHAD methodology. It is sometimes necessary to take into account ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…Though alloy 12 was slightly off-equilibrium, results from this alloy revealed that the tie-line of NbFe (m) with Zr(NbFe) 2 is impossible. This was consistent with our previous conclusion, in which the co-existence of bNb and NbFe (m) with (Zr 1Àx Nb x ) 2 Fe was observed [13], but is contradictory to that of Toffolon et al [12], who suggested equilibrium of NbFe (m) and bNb and Zr(NbFe) 2 . This conclusion was also substantiated by the phase identification in alloy 21, in which (Zr 1Àx Nb x )Fe 2 and bNb were detected.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Though alloy 12 was slightly off-equilibrium, results from this alloy revealed that the tie-line of NbFe (m) with Zr(NbFe) 2 is impossible. This was consistent with our previous conclusion, in which the co-existence of bNb and NbFe (m) with (Zr 1Àx Nb x ) 2 Fe was observed [13], but is contradictory to that of Toffolon et al [12], who suggested equilibrium of NbFe (m) and bNb and Zr(NbFe) 2 . This conclusion was also substantiated by the phase identification in alloy 21, in which (Zr 1Àx Nb x )Fe 2 and bNb were detected.…”
Section: Resultssupporting
confidence: 88%
“…They suggested that NbFe(m) equilibrated with Zr(NbFe) 2 . This [12] is different from our previous results, where we found that NbFe did not equilibrate with Zr(NbFe) 2 [13]. To obtain a more accurate thermodynamic description of the ZreNbeFe system, it is necessary to further experimentally investigate the phase equilibria in ZreNbeFe system.…”
Section: Introductioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The element peaks of Fe, Nb, and Zn can be found in the particles. Due to the easy dissolution of Sn atoms in the Zr matrix, it is difficult to detect Sn in the particles [21,22]. Thus, these particles should be the alloy compounds of Zr, Nb, and Fe elements in these two kinds of modified N36 Zr alloys.…”
Section: Resultsmentioning
confidence: 99%